2008
DOI: 10.1038/bjp.2008.43
|View full text |Cite
|
Sign up to set email alerts
|

Structural requirements for the cytoprotective actions of mono‐unsaturated fatty acids in the pancreatic β‐cell line, BRIN‐BD11

Abstract: Background and purpose: Exposure of pancreatic b-cells to long-chain free fatty acids leads to differential responses according to the chain length and degree of unsaturation. In particular, long-chain saturated molecules such as palmitate (C16:0) cause apoptosis, whereas equivalent mono-unsaturated species (for example, palmitoleate (C16:1)) are not overtly toxic. Moreover, mono-unsaturates exert a powerful cytoprotective response against a range of proapoptotic stimuli. However, the structural requirements t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
60
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(68 citation statements)
references
References 45 publications
7
60
0
1
Order By: Relevance
“…However, the situation is complex since studies with isolated human islets, primary rat b-cells and various b-cell lines have demonstrated that certain long-chain saturated fatty acids have the greatest propensity to induce cytotoxicity, while shorter chain saturated molecules (!C14) and long-chain unsaturated species are much less damaging. Indeed, some unsaturated fatty acids are potently cytoprotective and can attenuate the loss of viability caused by their saturated counterparts (Maedler et al 2003, Welters et al 2004, Diakogiannaki et al 2007, Dhayal et al 2008. This implies that fatty acids exert differential effects according to their chain length and degree of unsaturation but the mechanisms that underlie these differences have not been defined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the situation is complex since studies with isolated human islets, primary rat b-cells and various b-cell lines have demonstrated that certain long-chain saturated fatty acids have the greatest propensity to induce cytotoxicity, while shorter chain saturated molecules (!C14) and long-chain unsaturated species are much less damaging. Indeed, some unsaturated fatty acids are potently cytoprotective and can attenuate the loss of viability caused by their saturated counterparts (Maedler et al 2003, Welters et al 2004, Diakogiannaki et al 2007, Dhayal et al 2008. This implies that fatty acids exert differential effects according to their chain length and degree of unsaturation but the mechanisms that underlie these differences have not been defined.…”
Section: Discussionmentioning
confidence: 99%
“…This concept is important since it has emerged that b-cell lipotoxicity results from the activation of specific proapoptotic pathways that are differentially regulated by saturated and monounsaturated molecules. Thus, while long-chain saturated fatty acids such as palmitate (C16:0) and stearate (C18:0) are powerfully lipotoxic to pancreatic b-cells, the equivalent monounsaturated molecules (palmitoleate (C16:1) and oleate (C18:1)) are potently cytoprotective under in vitro conditions (Welters et al 2004, Diakogiannaki et al 2007, Dhayal et al 2008. In the present work, we have investigated the possibility that this may reflect a differential activation of the integrated stress response by saturated and monounsaturated fatty acids.…”
Section: Introductionmentioning
confidence: 99%
“…For example, GPR40 is known to be activated by both saturated and unsaturated fatty acids but only the latter are cytoprotective [75]. Furthermore, methylated fatty acids do not activate GPR40 whereas they are equipotent with underivatised molecules Page 11 of 34 A c c e p t e d M a n u s c r i p t as mediators of cytoprotection [76]. On this basis, it seems unlikely that GPR40 plays a major role in protecting β-cells against toxic insults.…”
Section: Role Of Gpr40 In Lipotoxicitymentioning
confidence: 99%
“…However, firm evidence to support this hypothesis is entirely lacking. Indeed, the demonstration that methyl-esters of unsaturated fatty acids are extremely potent cytoprotective agents in the β-cell [146] argues against this possibility since these fatty acids do not activate GPR120. Thus, at present its role in β-cells remains enigmatic.…”
Section: Gpr120mentioning
confidence: 99%
“…These compounds have been reported for several biological activities such as antioxidant, antitumor, cytotoxic, antimitotic (González et al, 2010), antibacterial (Gu& Wang, 2010, cytoprotective (Dhayal et al, 2008), anti-inflammatory (Hua et al, 2006) and so on.…”
Section: Resultsmentioning
confidence: 99%